2005
DOI: 10.1007/s11745-005-1434-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of rapeseed oil on metabolism of [1‐14C]18∶1n−9, [1‐14C]20∶3n−6, and [1‐14C]20∶4n−3 in atlantic salmon heaptocytes

Abstract: Atlantic salmon were fed fish meal-based diets supplemented with either 100% fish oil (FO) or 100% rapeseed oil (RO) from an initial weight of 85 g to a final average weight of 280 g. The effects of these diets on the capacity of Atlantic salmon hepatocytes to elongate, desaturate, and esterify [1-14C] 18:1n-9 and the immediate substrates for the delta5 desaturase, [1-14C] 20:3 n-6 and [1-14C] 20:4n-3, were investigated. Radiolabeled 18:1n-9 was mainly esterified into cellular TAG, whereas the more polyunsatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…There was also a tendency to higher production of 18:4n-3 in the high OA groups than in the high DHA groups. These results are in agreement with previous studies showing that vegetable oil can stimulate elongase and desaturase activity and/or gene expression [10,16,20,44,45]. No differences were found in DHA production between the four groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There was also a tendency to higher production of 18:4n-3 in the high OA groups than in the high DHA groups. These results are in agreement with previous studies showing that vegetable oil can stimulate elongase and desaturase activity and/or gene expression [10,16,20,44,45]. No differences were found in DHA production between the four groups.…”
Section: Discussionsupporting
confidence: 93%
“…This FA is the most abundant FA in rapeseed oil, which is the most common oil substitute in today’s aquaculture. The capacity for conversion of ALA to EPA and DHA, and the gene expression of the elongases, the Δ5- and Δ6fad activities in salmon is increased when fed high dietary levels of vegetable oils, while FOs depressed the capacities [6,1820]. Similar results have been found by Zheng et al [21], showing that EPA suppressed LC-PUFA synthesis in salmon cells and also suppressed the activity of the salmon Δ6fad promoter.…”
Section: Introductionsupporting
confidence: 65%
“…The impact of these changes of aquafeed ingredients on the composition of the fish and ultimately the impacts on the health of the consumers have not yet been explored in great detail. There is apparently some capacity for LC n -3 production from vegetable oils [58,59,60] in some fish, so this potential remains to be explored and developed.…”
Section: Fish Quality and Sustainabilitymentioning
confidence: 99%
“…Several studies have reported that most salmonids held in freshwater potentially have the ability to convert C18: 3n‐3 (α‐linolenic acid) from vegetable oil into the corresponding C20:5 n‐3 (EPA) and C22:6 n‐3 (DHA) in vivo by an alternating succession of desaturation and elongation (Ruyter & Thomassen ; Nakamura & Nara ; Moya‐Falcón et al . , ; Farrell et al . ; Codabaccus et al .…”
Section: Towards Increased Sustainability Of Feeding Salmonidsmentioning
confidence: 99%